Composition of Bottom Gillnet Catches Based on Different Fishing Grounds in Kuala Tungkal Waters, Tanjung Jabung Barat Regency, Jambi Province - Harry Decosta Simbolon; Arthur Brown; Bustari Bustari (Berkala Perikanan Terubuk, 2021)
This research was conducted from 4 March to 18 March 2021 in Kuala TungkalWaters, Tanjung Jabung Barat Regency, Jambi Province. The purpose of thestudy was to determine the composition of the catch types of bottom gill netswith different fishing areas, by looking at the number of catches using bottomgill nets. The composition of the catches in the fishing area at Boyar Beach onthe bottom gill nets for 8 days of catching is Happyin (LeutheronemaTetradactylum), Gerut (Pomadasys Maculatus), Malung (Muraenesox Cinereus)Jahan (Muraenesox Bagiu), Otek (Pomadasys Hasta), Parang (Netumathalassima) , and Talang (Chrisonemus Tolooparah), with a total weightof 108.8 kg as many as 152 tails. While the catches of the Alang Tiga CatchmentArea are Tenggiri (Scomberomorus Commersonip), Parang (Netumathalassima),Bagok (Netumathalassima), Alu-Alu (Sphyraena), Baji-Baji (PlatycephalusIndicus Linnaeus), Malung (Muraenesox Bagio) and Otek (Pomadasys cubits),with a total weight of 240.2 kg as many as 314 tails. The results of the studyconcluded that the composition of the catch was more on 11 GT vesselscompared to 6 GT vessels, because 11 GT vessels had a longer fishing area than6 GT vessels and the length of operation.